Uganda - Small Towns Water and Sanitation - Mohan, P.C. (2012)
The specific objectives of this project (Credit of US$42.3 million over the period 1995-2003) were to: (a) improve health conditions through better water supply, excreta disposal, waste management and public hygiene; (b) alleviate poverty and improve the lot of women; and (c) reduce environmental degradation through better waste management. The project was to provide improved and sustainable water supply and sanitation services in two groups of towns: (a) the 11 small towns ( Busia, Kalisizo, Kyotera, Lugazi, Luwero, Lyantonde, Malaba, Ntungamo, Rakai, Rukunguri and Wobulenzi ), where most of the town populations drew water from boreholes with hand pumps, springs and traditional sources such as rivers and lakes - this was to be implemented by the Directorate of Water Development ( DWD ); and (b) the rehabilitation of the water sewerage services in Jinja, to be expanded to include Njeru.- to be implemented by the National Water and Sewerage Corporation ( NWSC ).